Penerapan Konservasi Forest Dragon (Gonocephalus Chamaeleontinus) Secara Ex-Situ di Kota Bandung - Dara Dinanti; Tri Cahyanto (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
Action to protect and preserve flora and fauna are through conservation. Gonocephalus chamaeleontinus, or forest dragon, is a protected species that is endangered. However, due to limited space, conservation of this wildlife is conducted ex situ in Bandung City. The habitat at the conservation site is designed to mimic its natural habitat. Despite clear differences in temperature and climate between its original habitat and the conservation area, this species can still thrive well. Furthermore, there are no signs indicating stress in these animals due to environmental differences as they have already adapted to the habitat in ex situ conservation.